Multiple mechanisms of aminoglycoside ototoxicity are distinguished by subcellular localization of action - Wu, Patricia; Barros-Becker, Francisco; Ogelman, Roberto; Camci, Esra D.; Linbo, Tor H.; Simon, Julian A.; Rubel, Edwin W.; Raible, David W. (Frontiers in Neurology, 2024)
Mechanosensory hair cells of the inner ears and lateral line of vertebrates display heightened vulnerability to environmental insult, with damage resulting in hearing and balance disorders. An important example is hair cell loss due to exposure to toxic agents including therapeutic drugs such as the aminoglycoside antibiotics neomycin and gentamicin and antineoplastic agents. We describe two distinct cellular pathways for aminoglycoside-induced hair cell death in zebrafish lateral line hair cells. Neomycin exposure results in death from acute exposure with most cells dying within 1 h of exposure. By contrast, exposure to gentamicin results primarily in delayed hair cell death, taking up to 24 h for maximal effect. Washout experiments demonstrate that delayed death does not require continuous exposure, demonstrating two mechanisms where downstream responses differ in their timing. Acute damage is associated with mitochondrial calcium fluxes and can be alleviated by the mitochondrially-targeted antioxidant mitoTEMPO, while delayed death is independent of these factors. Conversely delayed death is associated with lysosomal accumulation and is reduced by altering endolysosomal function, while acute death is not sensitive to lysosomal manipulations. These experiments reveal the complexity of responses of hair cells to closely related compounds, suggesting that intervention focusing on early events rather than specific death pathways may be a successful therapeutic strategy.